Graded diacylglycerol kinases α and ζ activities ensure mucosal‐associated invariant T‐cell development in mice. Issue 2 (21st November 2019) - Pan, Yun; Deng, Wenhai; Xie, Jinhai; Zhang, Shimeng; Wan, Edwin C.K.; Li, Lei; Tao, Huishan; Hu, Zhiming; Chen, Yongping; Ma, Li; Gao, Jimin; Zhong, Xiao‐Ping
Abstract: Mucosal‐associated invariant T (MAIT) cells participate in both protective immunity and pathogenesis of diseases. Most murine MAIT cells express an invariant TCRVα19‐Jα33 (iVα19) TCR, which triggers signals crucial for their development. However, signal pathways downstream of the iVα19TCR and their regulation in MAIT cells are unknown. Diacylglycerol (DAG) is a critical second messenger that relays the TCR signal to multiple downstream signaling cascades. DAG is terminated by DAG kinase (DGK)‐mediated phosphorylation and conversion to phosphatidic acid. We have demonstrated here that downregulation of DAG caused by enhanced DGK activity impairs late‐stage MAIT cell maturation in both thymus and spleen. Moreover, deficiency of DGKζ but not DGKα by itself causes modest decreases in MAIT cells, and deficiency of both DGKα and ζ results in severe reductions of MAIT cells in an autonomous manner. Our studies have revealed that DAG signaling is not only critical but also must be tightly regulated by DGKs for MAIT cell development and that both DGKα and, more prominently, DGKζ contribute to the overall DGK activity for MAIT cell development. Abstract : Diacylglycerol kinases (DGKs) terminate diacylglycerol (DAG) by conversion to phosphatidic acid (PA). Uncontrolled DGKζ activity inhibits MAIT cell maturation from stage 2 to stage 3. Absence of both DGKα and ζ blocks MAIT cell maturation weakly from stage 1 to stage 2 but severely from stage 2 to stage 3.